Which assessment tools address the categories of the Brief ICF Core Set for Hand Conditions?. (September 2015) - van de Ven-Stevens, Lucelle AW; Kus, Sandra; Graff, Maud; Geurts, Alexander CH
Introduction: The purpose of this study was to explore whether assessment tools address aspects that are relevant according to the Brief ICF Core Set for Hand Conditions (BICF-CS). Methods: Assessment tools meant to assess functioning and/or environmental factors in adults with hand conditions were reviewed. MEDLINE and CINAHL databases, previously published reviews, the book Clinical Assessment Recommendations of the ASHT, and websites of assessment tools were used for the content comparison and linking to the 23 categories of the BICF-CS. The updated version of the linking rules was applied by two reviewers. Results: Forty-six assessment tools, known within the areas of hand therapy and hand surgery, were linked to the 23 categories of the BICF-CS. Regarding Body functions and body structures, the categories that were most frequently addressed were b730 "Muscle power functions, " b280 "Sensation of pain, " b710 "Mobility of joint functions, " and s730 "Structure of upper extremity . " Regarding Activities and Participation, d440 "Fine hand use" was addressed mostly and 25 assessment tools (with a total of 146 items) were linked to this category. Regarding Environmental Factors, only one assessment tool was identified that could be linked to two categories. Fifteen points of discussion were encountered in the linking process. Conclusions: Content comparison of 46 assessment tools revealed that 19 of the 23 categories of the BICF-CS were addressed. The environmental factors were hardly addressed.